Jane Pickeringe's lute book c. 1616-c. 1650 - Pickeringe, Jane; Spencer, Robert 1932-1997 (Kilkenny Boethius Press, 1985)
Jane Pickeringe's lute book c. 1616-c. 1650 (London, British Library, MS Egerton 2046) : containing 81 solos for Renaissance lute in G tuning, c. 1616-20 ... and 26 solos for 10- to 12- course lute in the variant tunings, c. 1630-50 ...